Tongue Acupuncture for the Treatment of Poststroke Aphasia: A Systematic Review and Meta-Analysis. (3rd October 2022) - Yang, Shengping; Li, Li; Jiang, Rong; Ding, Haoying; Xu, Fei; Ge, Lulu; Kuang, Peng; Wang, Zuhong
Abstract : Objective. This review evaluated the efficacy of tongue acupuncture for the clinical treatment of poststroke aphasia. Methods . PubMed, Medline, Cochrane, Embase, CNKI, VIP, and Wanfang databases were searched from their inception to 1st June 2022. The dataset included randomized controlled trials (RCTs) with tongue acupuncture for the treatment of poststroke aphasia. Data aggregation and risk of bias evaluation were conducted on Review Manager Version 5.4.1 and Stata16.0. The main outcome measures included the Aphasia Battery of Chinese (ABC), the Chinese Functional Communication Profile (CFCP), the Boston Diagnostic Aphasia Examination (BDAE), and clinical efficiency. Then, comparing the effectiveness of tongue acupuncture, tongue acupuncture combined with conventional therapies, conventional therapies with head acupuncture, language training, body acupuncture, and Jie Yu Dan. Results . A total of 20 studies with 1355 patients were included. Meta-analysis showed that compared with conventional treatments, tongue acupuncture has a significant improvement in clinical efficacy score (MD = 1.25, 95% CI (1.09, 1.43), P = 0.001 ) and CFCP of poststroke aphasia (MD = 39.78, 95% CI (26.59, 52.97), P < 0.00001 ), but was not significant in improving ABC (MD = 5.95, 95% CI (2.85, 9.04), P = 0.06 ). Compared to the conventional treatments, tongue acupuncture combined with conventional therapies promoted the ABC (MD = 11.48, 95% CI (2.20, 20.75), P < 0.00001 ), clinical efficacy score (MD = 1.22, 95% CI (1.14, 1.30), P < 0.00001 ), and CFCP score (MD = 29.80, 95% CI (19.08, 40.52), P < 0.00001 ) of poststroke aphasia. Conclusion . This systematic review indicated that tongue acupuncture or tongue acupuncture combined with conventional treatments was an effective therapy for treating poststroke aphasia. However, stricter evaluation standards and rigorously designed RCTs are needed.